EFEKTIVITAS MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) DENGAN MEDIA PERMAINAN PADA POKOK BAHASAN PERSAMAAN GARIS LURUS - Rusdiyana, Erine; Trapsilasiwi, Dinawati; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2018)
Abstract. Based on interview results, some students said that gradient was the most difficulted topic. It caused by learning model that teacher used is monotonous and too bored, that’s why we need Missouri Mathematics Project (MMP) with games media to solve the problem. Through the games media, students are expected to be easily in understanding mathematical concepts especially to solve problems that related to the topic of gradient. This study aims to knowing the effectiveness of MMP’s learning model with games media on Equation of Straight Line’s topic for student’s mathematics learning outcomes. This research is a pure experimental research with Posttest-only control design design. The population are all of students in second class of SMP Negeri 1 Banyuglugur. Sampling is choosed by cluster random sampling technique. The sample consisted of 2 kinds of class. Hypothesis testing method that used in this research is T test (One Sample Test). This research show that H0 was rejected with tcount = 3,416 > ttable = 2,060 and p-value = 0,002 ˂ 0,025. It means that the learning model of MMP with games media on Equation of Straight Line’s topic is effective for student’s mathematics learning outcomes. Keyword: Missouri Mathematics Project (MMP), Game Media, Equation of a Straight Line